2021
DOI: 10.1136/thoraxjnl-2020-216639
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic differences in lung function metrics: evidence from two cohorts

Abstract: RationaleThe biochemical mechanisms underlying lung function are incompletely understood.ObjectivesTo identify and validate the plasma metabolome of lung function using two independent adult cohorts: discovery—the European Prospective Investigation into Cancer–Norfolk (EPIC-Norfolk, n=10 460) and validation—the VA Normative Aging Study (NAS) metabolomic cohort (n=437).MethodsWe ran linear regression models for 693 metabolites to identify associations with forced expiratory volume in one second (FEV1) and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…For instance, our metSS was developed in a population enriched with COPD, which could limit the generalizability and the deconvolution of those metabolomic pathways related to COPD progression versus those that regulate lung development and variability in the general population. This is supported by the overall low, but not negligible, overlap of metabolites associated with FEV 1 between our analysis and those involving general population cohorts that included a significant proportion of individuals who never smoked and/or who had normal FEV 1 [ 5 , 6 ]. Beyond disease progression versus lung-development-related metabolites, differences in methodological approaches (adaLASSO vs. multivariable regression models) between analyses might also explain these results and warrant further investigation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…For instance, our metSS was developed in a population enriched with COPD, which could limit the generalizability and the deconvolution of those metabolomic pathways related to COPD progression versus those that regulate lung development and variability in the general population. This is supported by the overall low, but not negligible, overlap of metabolites associated with FEV 1 between our analysis and those involving general population cohorts that included a significant proportion of individuals who never smoked and/or who had normal FEV 1 [ 5 , 6 ]. Beyond disease progression versus lung-development-related metabolites, differences in methodological approaches (adaLASSO vs. multivariable regression models) between analyses might also explain these results and warrant further investigation.…”
Section: Discussionsupporting
confidence: 68%
“…KEGG analysis also identified aminoacyl-tRNA biosynthesis and glycine, serine, and threonine pathway overrepresentation in the metSS, which suggests disturbances in general amino acid metabolism. Aminoacyl-tRNAs are vital for protein synthesis and have been associated with oxidative stress [ 5 , 6 , 26 ]. Similarly, multiple studies have found enrichment of the glycine, serine, and threonine metabolism pathways, which have been associated with COPD exacerbation severity [ 4 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depression and anxiety subscales comprised six questions in total, and the phobic anxiety subscale comprised five questions. The scores were categorized as “abnormal” on a given subscale if the score was one standard deviation (SD) above the sample mean, as previously defined [ 24 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“… Note: Individuals are categorized as having an abnormal score on a given BSI subscale if their score is one standard deviation above the mean, as previously described in [ 24 , 26 , 27 ]. …”
Section: Figurementioning
confidence: 99%